Factors Associated with Psychological Distress of Online Drivers in Medan Regency, North Sumatera, Indonesia - Saragih, Fenny Aprilia; Loebis, Bahagia; Camellia, Vita; Effendy, Elmeida (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: In developing countries, public health issues that are often discussed about psychological distress that can be characterized by anxiety, sadness, stress, depression, and confusing feelings. Online drivers have the potential to experience the stress of psychological distress. The individual is faced with various pressures from work or family such as competition between transportation to get passengers daily, long working time to achieve the target leads, the obligation to pay off the loan, and responsibilities to family needs often cause stress. Method: This study was a multivariate type of predictive analysis to finding out factors associated with GHQ-12 scores of the online drivers with 110 samples who have fulfilled inclusion and exclusion criteria. Results: Found the factors associated with psychological distress that is marital status, number of family members, length of education, working experience, age, length of work/day, daily target achievement, and total income/month of online drivers Conclusion: From the results of this study it was found that the most associated factors with psychological distress scores are total income/month.